Improvement of the amino acid composition of a mung bean-based functional beverage through the application of a metabolic modulator during sprouting - Makenova, Aliya; Mussayeva, Saltanat; Dautkanova, Dina; Ussembayeva, Zhibek; Dautkanov, Nurlan (Eastern-European Journal of Enterprise Technologies, 2026)
The object of this study is sprouted mung bean seeds (Vigna radiata L.) of the “Zhasyl dän” variety, used as a raw material for developing a functional beverage with improved protein quality. The study addresses the limited biological value of plant proteins associated with their amino acid composition Seeds were germinated in distilled water (control) and in a 2% sucrose solution for 24, 48, and 72 hours. Amino acid composition was analyzed using high-performance liquid chromatography (HPLC) with fluorescence detection. Sucrose addition led to a clear increase in amino acid content during germination, with the strongest effect observed after 48 hours. Total amino acid content increased from 21,539 to 26,656 mg/100 g dry weight (+23.8%). The most noticeable changes were found for essential amino acids, including lysine (+20.7%), valine (+23.9%), and branched-chain amino acids (leucine and isoleucine, +26.2%). Glutamic and aspartic acids also increased by about 24%, which may be linked to improved taste characteristics. In general, sucrose influenced metabolic processes and resulted in a 20–25% increase in amino acid content without the use of microbial cultures. The optimal germination time was around 48 hours. These results suggest that controlled germination with carbohydrate addition can be used as a simple approach to improve plant protein quality in functional food products.